2010
DOI: 10.1002/pssc.200982658
|View full text |Cite
|
Sign up to set email alerts
|

Study of phase separation and photo‐ luminescent emission in silicon nanostructured PECVD systems

Abstract: In this work two systems with total phase separation composed of alternated a‐Si/SiO2 and a‐Si/Si3N4 respectively along with silicon‐rich SiOxNy films were deposited by the PECVD technique and characterized by XANES, Raman, TEM and PL techniques. The multilayers were used to analyse the effects of phase separation in the XANES and Raman spectra as well as to determine the phase contrast in TEM images in order to elucidate upon the existence of phase separation in the silicon‐rich SiOxNy films and correlate it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…As discussed in previous works (10,11) the phase separation and the small size of the silicon clusters are responsible for the optical modifications on the photoluminescence of Si-rich SiO x N y films, and Raman spectroscopy has shown to be very sensitive to the local atomic arrangement in the study of those films. A band s in the 400 cm -1 to 550 cm -1 range , corresponding to Si-Si bonds vibrations, is observed for all the studied films, for bulk amorphous silicon the signal due to Si-Si bonds is a wide band centered at 480 cm -1 , for small amorphous silicon clusters this signal shifts towards lower wavenumber , Si-Si bonds arranged in silicon single crystal peak at 520 cm -1 , and nano-or microcrystals appear in the range from 490 cm -1 to 510 cm -1 .…”
Section: Ecs Transactions 39 (1) 123-129 (2011)mentioning
confidence: 82%
See 1 more Smart Citation
“…As discussed in previous works (10,11) the phase separation and the small size of the silicon clusters are responsible for the optical modifications on the photoluminescence of Si-rich SiO x N y films, and Raman spectroscopy has shown to be very sensitive to the local atomic arrangement in the study of those films. A band s in the 400 cm -1 to 550 cm -1 range , corresponding to Si-Si bonds vibrations, is observed for all the studied films, for bulk amorphous silicon the signal due to Si-Si bonds is a wide band centered at 480 cm -1 , for small amorphous silicon clusters this signal shifts towards lower wavenumber , Si-Si bonds arranged in silicon single crystal peak at 520 cm -1 , and nano-or microcrystals appear in the range from 490 cm -1 to 510 cm -1 .…”
Section: Ecs Transactions 39 (1) 123-129 (2011)mentioning
confidence: 82%
“…In previous works we reported that Si-rich SiO x N y films present intense (photoluminescence) PL, attributed to phase separation in small silicon clusters embedded in the insulator matrix and consequent quantum confinement effects (10,11). Also high photo-luminescent intensity in SiN x films even more intense than in SiO x N y was observed and attributed to dispersed amorphous silicon clusters in the dielectric SiN x matrix.…”
Section: Introductionmentioning
confidence: 78%
“…The phase separation and the small size of the silicon clusters are responsible for the optical modifications of the photoluminescence of silicon based films, and Raman spectroscopy has shown to be very sensitive to the local atomic arrangement in the study of those films [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…This technique presents some advantages compared to UV-laser ablation such as low deposition cost, good thickness control, possibility of producing films of complex stoichiometry (such as highTc superconductors, intermetallic alloys and glasses), the absence of the dangerous gasses pervading CVD techniques [12], and low deposition temperature. This technique is a process in which a high power electron beam (15)(16)(17)(18)(19)(20) is pulsed producing the volatilization of the impacted region of the material. In this work we study the formation of silicon clusters in the film and the influence of the deposition process on the photoluminescence.…”
Section: Introductionmentioning
confidence: 99%